Biologia Alimentar e Reprodutiva de Helicops angulatus (LINNAEUS, 1758) (Serpentes, Colubridae) da Amazônia Oriental, Pará - Abe, Pedro Santos (Museu Paraense Emílio Goeldi, 2023)
In order to study the feeding and reproductive biology of Helicops angulatus from the Eastern Amazon, 220 specimens from the herpetological collection of the Museu Paraense Emílio Goeldi were analyzed. The majority of the individuals presented anteroposterior direction of ingestion. There was a predominance of fish in the diet of H. angulatus, composed of the following Orders and families: Gymnotiformes - Gymnotidae; Perciformes - Cichlidae; Siluriformes - Callichthyidae; Characiformes - Erythrinidae, Lebiasinidae, Curimatidae. All fish species identified live in lentic environments and most forage at the bottom of the water column. Three individuals had anurans in their stomach contents, belonging to the following families and genera: Leptodactylidae -Adenomera, Bufonidae - Bufo, and Hylidae - Hyla. These genera are found in the burlap and shrubs, which indicates that H. angulatus also forages in the terrestrial environment. Mature females showed significantly higher CRC than mature males (t= 6.12; p<0.05). The COCD of males was relatively larger than that of females (t=6.1; p<0.05). Females have a greater number of ventral scales than males (t= 3.5; p<0.05), and males have a greater number of subcaudal scales than females (t= 6.0; p<0.05). Females with vitellogenic follicles, eggs and young were found throughout the year, indicating that the species has an aseasonal reproductive cycle. They present high fecundity ranging from 5 to 14 eggs. There was no significant difference between the number of vitellogenic follicles and the number of eggs (Mann-Whitney: U = 107.0; Z = 1.05; P = 0.29), and therefore most vitellogenic follicles converge and eggs. The number of vitellogenic follicles and/or eggs showed no relationship with the rostro-cloacal length of the females.